Textual Analysis of Three Poems by M. Sereshk from the Point of View of Linguistic and Cognitive Foundations - Vahidi, Ahmadnoor; Salimi, Hossein; Alavi, Bashir (LANGUAGE ART, 2020)
This article examines the components of linguistic theory with a different approach in Shafiei Kadkani’s three poems. The study of the knowledge of these propositions is done in the framework of the theory of George Lakoff and Johnson. In this context, cognitive analysis of the text is discussed in several discussions of schemas, cognitive metaphor, metaphorical individuality and its motifs. . By reading this kind of critique, in terms of mapping the system and the flow of linguistic cognition to the intellectual world and drawing the structure of the poet’s poetry can be achieved. . This study shows how the linguistic elements and prominence’s of language and the orienting schemas and metaphors that are the foundations of cognition can relate the form and content and beliefs of the author to the automated language and prove that similarities And the similarity of the examples of this theory in the discussion of schemas and metaphors in these three poems of Shafiei Kadkani is obvious and it can be seen that the form of these three poems is in proportion with the currents of formalism which is the output of the foundations of cognitive linguistics. . Evidence shows that in addition to the presence of directional metaphors and different schemas in Shafiei poetry, the occurrence of several schemas and metaphors on a similar text has been created and metaphors, in addition to modernity in the flow of the text, They have not given a clear ideology. In this research, samples are extracted from the Shafiei Kadkani poems in accordance with this concept. This article has been done by descriptive and analytical method.